2022
DOI: 10.1099/ijsem.0.005182
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrobacter albicanus sp. nov., isolated from Antarctic soil

Abstract: A Gram-stain positive, strictly aerobic, non-motile and rod-shaped strain, NJ-Z5T, was isolated from a soil sample obtained from the Antarctic Peninsula. This strain was taxonomically characterized by a polyphasic approach. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NJ-Z5T belonged to the genus Pseudarthrobacter and showed the highest similarities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The major polar lipid profile of RMG13 T was similar to those of the phylogenetically related type strains of species of the genus Pseudarthrobacter . However, the minor polar lipid profile differs from that of the phylogenetically related strains, supporting the hypothesis that the strain represents a novel species of the genus Pseudarthrobacter [6, 42]. The major fatty acid profile of RMG13 T contained anteiso-C 15 : 0 (44.1 %), iso-C 15 : 0 (16.4 %) and anteiso-C 17 : 0 (10.1 %).…”
Section: Full-textmentioning
confidence: 62%
See 1 more Smart Citation
“…The major polar lipid profile of RMG13 T was similar to those of the phylogenetically related type strains of species of the genus Pseudarthrobacter . However, the minor polar lipid profile differs from that of the phylogenetically related strains, supporting the hypothesis that the strain represents a novel species of the genus Pseudarthrobacter [6, 42]. The major fatty acid profile of RMG13 T contained anteiso-C 15 : 0 (44.1 %), iso-C 15 : 0 (16.4 %) and anteiso-C 17 : 0 (10.1 %).…”
Section: Full-textmentioning
confidence: 62%
“…According to LPSN (https://lpsn.dsmz.de/ genus/pseudarthrobacter), the genus Pseudarthrobacter currently comprises 13 species with validly published names. Members of this genus have been isolated from various sources, such as antarctic soil, veterinary clinic materials, sediments, other soils and filtration substrates [5][6][7][8][9][10]. Members of the genus Pseudarthrobacter are Gram-stain-positive, aerobic and rod-or coccusshaped.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have revealed that members of the genus Pseudarthrobacter can grow under a wide range of temperatures. For example, Pseudarthrobacter albicanus NJ-Z5 T isolated from Antarctic soil has been shown to grow at temperatures ranging from 4 to 28 °C 40 . Similarly, Pseudarthrobacter humi RMG13 T isolated from soil exhibited a capacity to grow within a temperature range of 4–37 °C 41 .…”
Section: Resultsmentioning
confidence: 99%